PENGARUH INDEPENDENSI, ETIKA AUDITOR, KOMPETENSI, PENGALAMAN AUDITOR DAN OBJEKTIVITAS TERHADAP KUALITAS AUDIT - Amorowati Dewi Pramesti, 14.05.52.0148; Alfasadun, Alfasadun (Students' Journal of Accounting and Banking, 2018)
This study aims to test and analyze empirically about the influence of independence, auditor ethics, competence, auditor experience and objectivity to audit quality (Empirical Study At Public Accounting Firm in Semarang City). Population used in this research is all auditor of KAP in Semarang City. The sampling method used is the convience sampling, which is the selection of samples based on convenience, so the authors have the freedom to choose the most rapid and easy sample. In this study the dependent variable used is audit quality, while the independent variables consist of independence, auditor ethics, competence, auditor experience, and objectivity. The results showed that independence had a non-significant positive effect on audit quality. Auditor ethics and auditor experience have a significant negative effect on audit quality. Competence and objectivity have a significant positive effect on audit quality. Keywords: independence, auditor ethics, competence, auditor experience, objectivity, and audit quality